1989
DOI: 10.1080/01688638908400908
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the wais and wais-r using t-score conversions that correct for age, education, and sex

Abstract: A newly developed T score conversion system that corrects Wechsler Adult Intelligence Scale (WAIS) and Wechsler Adult Intelligence Scale-Revised (WAIS-R) subtest and IQ scores for appropriate demographic variables was used to compare subjects' performance on the two versions of the instrument. Using 428 pairs of subjects matched on age, education, and sex, with one person in each pair having taken the WAIS and the other the WAIS-R, we found no significant differences in level or pattern of performance when ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…Of the total sample, 35 (87.5%) of the schizophrenic patients were receiving medication at the time of intake. Thirty-four (85%) were receiving high-potency neuroleptic medications.…”
Section: Methodsmentioning
confidence: 99%
“…Of the total sample, 35 (87.5%) of the schizophrenic patients were receiving medication at the time of intake. Thirty-four (85%) were receiving high-potency neuroleptic medications.…”
Section: Methodsmentioning
confidence: 99%
“…The investigators found mean differences on the WAIS and WAIS-R of 6.4, 3.5, and 5.8 points between the VIQs, PIQs, and FSIQs, comparable to the differences noted by tke other investigators. Thompson, Heaton, Grant, and Matthews, 1989 later cautionkd that differences in IQs for the two versions might be due to the differences in the standardization samples and not differences in content of the scales. This hypothesis was supported by their finding that by using demographically corrected scores (for age, education, and gender), the comparability of WAIS and WAIS-R IQ scores for normal subjects was improved.…”
Section: Comparisons Between the Wais And The Wais-rmentioning
confidence: 96%
“…With the exception of the CVLT, all the raw scores on the NP tests were converted to age-, education-, and gender-corrected T scores (Heaton, 1992; Heaton et al, 1991; Thompson & Heaton, 1989). Age- and gender-corrected T or z scores were used for the CVLT (Delis et al, 1987).…”
Section: Methodsmentioning
confidence: 99%
“…Psychomotor skills: Tactual Performance Test (TPT) total time, Part A of the Trail Making Test, WAIS-R Block Design, WAIS-R Digit Symbol, and WAIS-R Object Assembly. With the exception of the CVLT, all the raw scores on the NP tests were converted to age-, education-, and gender-corrected T scores (Heaton, 1992;Heaton et al, 1991;Thompson & Heaton, 1989). Age-and gender-corrected T or z scores were used for the CVLT (Delis et al, 1987).…”
Section: Neuropsychological Measuresmentioning
confidence: 99%